2016
DOI: 10.3390/ijms17071040
|View full text |Cite
|
Sign up to set email alerts
|

Cell Models and Their Application for Studying Adipogenic Differentiation in Relation to Obesity: A Review

Abstract: Over the last several years, the increasing prevalence of obesity has favored an intense study of adipose tissue biology and the precise mechanisms involved in adipocyte differentiation and adipogenesis. Adipocyte commitment and differentiation are complex processes, which can be investigated thanks to the development of diverse in vitro cell models and molecular biology techniques that allow for a better understanding of adipogenesis and adipocyte dysfunction associated with obesity. The aim of the present wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
248
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(251 citation statements)
references
References 170 publications
(223 reference statements)
3
248
0
Order By: Relevance
“…Furthermore, chemicals or small molecules including cytokines are major factors in the induction of cell differentiation [25][26][27][28]. Francisco et al found that human preadipocytes and ASCs were excellent models for studying adipogenesis and obesity-related metabolic alterations and were appropriate for revealing adipocyte renewal, development and depot-specific differences [4]. Therefore, we focused on uncovering the molecular regulation mechanism as to how miRNAs regulate adipogenic differentiation of hASCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, chemicals or small molecules including cytokines are major factors in the induction of cell differentiation [25][26][27][28]. Francisco et al found that human preadipocytes and ASCs were excellent models for studying adipogenesis and obesity-related metabolic alterations and were appropriate for revealing adipocyte renewal, development and depot-specific differences [4]. Therefore, we focused on uncovering the molecular regulation mechanism as to how miRNAs regulate adipogenic differentiation of hASCs.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring the alteration of adipose-derived stem cells (ASCs) can provide a promising future in the field of tissue engineering and regenerative medicine [3]. First, ASCs are recruited by certain stimulation, following which they are transformed into preadipocytes and then ultimately turn into mature adipocytes [4]. During adipogenesis, several transcription factors such as peroxisome proliferator-activated receptor-γ (PPARγ) and members of the CCAAT/enhancer-binding family of proteins (c/EBPα) participate in regulating adipogenesis [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The 3T3-L1 is a cell line derived from mouse 3T3 cells, which is an adipocyte with fibroblast like morphology (Ruiz-Ojeda, Ruperez, Gomez-Llorente, Gil, & Aguilera, 2016). The fibroblast cell lines viz.…”
Section: In Vitro Wound Healing Assaymentioning
confidence: 99%
“…Results from these studies are not as useful for applications on human health as expected, given the physiological and metabolic differences among species [2]. Human primary cultured cells are the best resource to understand human adipocyte biology in deranged metabolic states [2], but cannot inform about cell events that occur during prenatal life.…”
Section: Introductionmentioning
confidence: 99%